If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(6xy + -12) + 3(5xy + 8) = 0 Reorder the terms: -1(-12 + 6xy) + 3(5xy + 8) = 0 (-12 * -1 + 6xy * -1) + 3(5xy + 8) = 0 (12 + -6xy) + 3(5xy + 8) = 0 Reorder the terms: 12 + -6xy + 3(8 + 5xy) = 0 12 + -6xy + (8 * 3 + 5xy * 3) = 0 12 + -6xy + (24 + 15xy) = 0 Reorder the terms: 12 + 24 + -6xy + 15xy = 0 Combine like terms: 12 + 24 = 36 36 + -6xy + 15xy = 0 Combine like terms: -6xy + 15xy = 9xy 36 + 9xy = 0 Solving 36 + 9xy = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + 9xy = 0 + -36 Combine like terms: 36 + -36 = 0 0 + 9xy = 0 + -36 9xy = 0 + -36 Combine like terms: 0 + -36 = -36 9xy = -36 Divide each side by '9y'. x = -4y-1 Simplifying x = -4y-1
| (6x+5)-1.3=-1.9 | | 0.33x+10=55 | | 14p^3q^3-21p^2q^2+35pq= | | 400-5x=322-3x | | 2(7)+6+5(7)=55 | | 8789-3434=876x | | -11-r=4(r-4) | | 1/4(3x+5)-1/3(x+7)=6 | | (m)=10 | | 33*.33n=.99n | | 25y^2+10y+1= | | 3x=54+3x | | 14x-28=-56 | | 6(z-4)+8z-3= | | 1/3(x-4)=5x-4(x-1)+22/3 | | 2(x-2)+3=2x+6 | | 2x+7+x=7 | | 22-3x=1 | | 0.5(10x+8)=3x-6 | | x^2(x+4)+2x(x+4)-15(x+4)= | | 11x-8x+19-2=5 | | 1/6(x+2)=2x-3(4-x)-7 | | 4d-7d+18=3 | | 8=8m+14-9m | | -3=w+3 | | 5(4x+2x)-(8x-12)=68 | | 4a+8b-16c= | | 96wx^3y^3z^2-144w^3xy^2z^3= | | -8y+-2x+3x+4y+2=3 | | 10x-9(x+6)=31 | | -3x+7+4x=2 | | 14x-28=56 |